Corpus Use and Learning to Translate, almost 20 years on - Patricia Rodríguez-Inés; Daniel Gallego-Hernández (Cadernos de Tradução)
It is almost 20 years since a series of conferences known as CULT (Corpus Use and Learning to Translate) started. The first and second took place in Bertinoro, Italy, back in 1997 and 2000, respectively. The third was held in 2004 in Barcelona, and the fourth in 2015 in Alicante. Each was organized by a few enthusiastic lecturers and scholars who also happened to be corpus lovers. Guy Aston, Silvia Bernardini, Dominic Stewart and Federico Zanettin, from the Universitá di Bologna; Allison Beeby, Patricia Rodríguez-Inés and Pilar Sánchez-Gijón, from the Universitat Autònoma de Barcelona; and Daniel Gallego-Hernández, from the Universidad de Alicante, organized CULT conferences in the belief that spreading the word about the usefulness of corpora for teaching and professional translation purposes would have positive results.